Faktor Penyebab Mahasiswi Merokok Dikalangan Fis Universitas Negeri Jakarta - Wahyu Ningsih; Abdul Haris F.; Nova Scorviana H. (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to obtain data on smoking behavior among female students of FIS State University Jakarta. To get a clear picture of smoking behavior and the factors that cause female students to smoke at the Faculty of Social Sciences, State University of Jakarta, researchers used a descriptive approach. Several data collection techniques were carried out with semi-structured interviews, participant observation, document analysis and field notes. This research was conducted for five months from January to June 2024. The results of the study concluded that there are two factors behind the behavior of female students to smoke. Internal factors are from within oneself and from the family. Relieving stress is the reason from within them to smoke. While the family is their support for smoking because family members who smoke encourage students to smoke. External factors also influence female students to smoke, namely from friends and cigarette advertisements themselves. Then there is a deviation of differential association because the process of female students to learn to smoke comes from family and friends, which proves that deviation can be done from the learning process.